A Case Report of Angiosarcoma of the Tongue: A Diagnostic Dilemma at Presentation - Shilajit Bhattacharya; Ajit V. Koshy; Prachi Baldawa; Samantha Thakur; Amisha Shah; Harshad Bhagwat (Indian Journal of Dental Research)
Rationale: Angiosarcoma is a malignant mesenchymal tumor arising from vascular endothelial cells. This is an aggressive malignancy associated with poor prognosis. Angiosarcoma in the head and neck is exceedingly rare, accounting for less than 4 % of tumors.[1] Patient Concern: We report a unique case of angiosarcoma involving the tongue underlying the diagnostic conundrum and pointers towards an accurate diagnosis. Take-away lesson: Due to rarity of the disease, consensus on optimal treatment approach is lacking and multicenter prospective studies would be helpful to set clinical guidelines.